HUBUNGAN ANTARA HIPERURIKEMIA DENGAN MICROALBUMINURIA PADA MASYARAKAT DESA LEGIAN KUTA BALI - Halim, Abd.; -, Kambayana; Raka Putra, Tjokorda (journal of internal medicine, 2011)
Microalbuminuria has been linking to cardiovascular (CV) risk in patients with diabetes or hypertension in unselectedgeneral population. Serum Uric Acid (UA) is an emerging novel risk factor for CV disease. The aim of our study was to evaluatethe correlations between hyperucemia and microalbuminuria in the adult Legian Kuta Village population. We selected eligible136 participants of adult (>18 years old) in Legian Kuta village who agreed to participate. We excluded diabetes mellitus,hypertension, urinary tract infection, and fever. We measured total cholesterol, HDL, LDL-cholesterol, triglyseride, fasting and2-hour post prandial blood sugar, serum creatinine, serum uric acid, systolc-diastolic blood pressure and microalbuminuria(Urinary Albumin/Creatinine Ratio, ACR).The prevalence of hyperuricemia in our study was 16.9 % while microalbuminuria was 5.1 % (ACR 30 ! 299 g/mgcreatinine) and macroalbuminuria 1.5% (ACR > 300 g/mg creatinine). Hyperuricemia and obesity signiÞ cantly correlated withmicroalbuminuria by Bivariate Analysis Spearmanrho correlation r = 0.274, p = 0.001; r = 0.178, p = 0.038 (p < 0.05) respectively.Age, sex, smoking, total cholesterol, LDL, HDL and triglyseride were not signiÞ cantly correlated with microalbuminuria (p >0.05). In a stepwise multiple logistic regression model, hyperuricemia to microalbuminuria remained signiÞ cantly correlatedwith R Square 0.280 and prevalence ratio 7.90; p = 0.013; 95% CI 1.54 ! 40.60. Obesity was not signiÞ cantly correlated withmicroalbuminuria p = 0.161; 95% CI 0.59 ! 23.03. Our study showed hyperuricemia was signiÞ cantly correlated, as independentpredictors to microalbuminuria.